Is remote ischaemic preconditioning of benefit to patients undergoing cardiac surgery? - Marczak, Jakub (Oxford University Press, 2012)
A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was whether remote ischaemic preconditioning (RIPC) is of benefit to patients undergoing cardiac surgery. Altogether, more than 264 papers were found using the reported search, 16 of which represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. We conclude that RIPC is a safe protocol which could potentially be used in cardiac surgery to provide additional cardiac protection against ischaemia reperfusion injury, although it may not be appropriate for patients on K(+) ATPase channel blockers (sulphonylureas) as they seem to eliminate the effect of RIPC. In our study, we found two meta-analyses of cardiac surgery with or without RIPC. Both unequivocally showed 0.81 and 0.74 standardized mean reduction in myocardial necrosis markers in patients receiving RIPC and cardiac or vascular surgery. No difference in perioperative myocardial infarction incidence or 30-day mortality were found. In adult cardiac surgery, we found 11 randomized control trials (RCTs) ranging in size from 45 to 162 patients. Two representative studies reported no difference in postoperative cardiac troponin I concentration in RIPC vs. controls. In one of the studies (CABG ± RIPC) no additional benefit could have been observed for RIPC regarding intra-aortic balloon pump usage (controls 8.5 vs. RIPC 7.5%), inotropic support (39 vs. 50%) or vasoconstrictor usage (66 vs. 64%). On the other hand, in the other study [CABG ± AVR (aortic valve replacement)  ± RIPC] significant reduction of troponin I at 8 h postoperatively (controls, 2.90 µg/l vs. RIPC, 2.54 µg/l, P = 0.043) was shown. Marked reduction in cardiac necrosis markers was also found in several smaller RCTs concerning coronary artery bypass grafting (CABG) patients receiving RIPC preoperatively: with cold crystalloid cardioplegia (44.5% reduction), with cross-clamping and fibrillation (43% reduction) and with cold blood cardioplegia (42.4% reduction). The proof of concept trials summarized here give some early evidence that RIPC may potentially provide some reduction in myocardial injury. If confirmed, in future clinical studies this technique may one day lead to a method to reduce reperfusion injury in clinical practice.